Análise das ações técnicas dos goleiros de futsal nos jogos escolares de Parintins de 2022 – juvenil masculino - Rodrigues, Alan Silva (Brasil, 2024)
The objective of this study was to analyze the technical actions of futsal goalkeepers who participated in the 2022 Parintins School Games, specifically in the male youth category. The analyzes were carried out during the 15 matches involving 10 school teams participating in the competition. To characterize the goalkeepers' performances, the data collected during the matches were adapted to the scout proposed by the author of this research based on the model by D’Avila et al (2002), as a way of guiding the analysis. In this study, the following factors were analyzed: finishing, finishing area, location of the goal scored. The result was divided into: goal, goalkeeper save, shot away and shot on target. A total of 514 completions were obtained, 233 of which were correct. Finishing area 2 was where there was the highest percentage of finishes with 22.18%. Regarding the location of the goal where the shots hit, location 4 stood out with 23.60%. From the number of successful shots, 26.18% of goal conversions were obtained, with 62.23% of saves made by goalkeepers. It is concluded that the goal location where goalkeepers managed to be most effective with their defensive actions was location 8 (94.12%). The place with the highest occurrence of goals in the School Games was in area 1 (19.68%) and area 4 (29.50%). The types of defenses most performed by goalkeepers were low saves without falling (DBSQ) with 8.05% and medium defense without falling (DMSQ) with 7.28%.